The Urgency of The Existence of Approval of Medical Actions In Palliative Services - Rindianti, Devy Febrina; Nugraheni, Ninis (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
for humanity. All actions of palliative care carried out by the palliative team, really need informed consent, so that they are not subject to administrative, criminal or civil sanctions. So in this study the aims were to analyze the legal ratio of informed consent in palliative care based on the Minister of Health Decree number 812/Menkes/SK/VII/2007 concerning Palliative Care Policy, and analyze legal liability for negligence in making informed consent in palliative care. The research method is normative juridical with a statute approach and conceptual approach. The results of this study are that in the process of palliative care carried out with multidisciplinary knowledge, these actions really require informed consent. And legal responsibility for negligence in making informed consent in palliative care can be in the form of administrative, criminal or civil sanctions.